Learner Autonomy in the Age of AI: How GenAI Tools Reshape Self-Regulated Learning Strategies in EFL Academic Writing - Jati Suryanto (Journal of Innovation in English Education and Language Teaching, 2026)
The rapid uptake of generative AI tools in higher education has prompted urgent questions about learner autonomy and self-regulated learning (SRL) in EFL academic writing contexts. This study investigates how access to GenAI tools reshapes the self-regulated learning strategies of undergraduate EFL writers at a public Islamic university in Indonesia, with particular attention to goal-setting, monitoring, resource management, and help-seeking behaviours. Using a longitudinal qualitative design with sixteen participants followed across one academic year, the study draws on learning journals, stimulated recall interviews, and writing process traces to map how SRL strategies shifted as participants integrated GenAI tools into their academic writing practice. Findings reveal four patterns of SRL reorganisation: strategic augmentation, in which GenAI was incorporated as one resource among many within a developed self-regulatory repertoire; passive substitution, in which GenAI progressively replaced rather than supplemented self-regulatory effort; anxious avoidance, in which learners with high writing anxiety selectively used GenAI to manage affective load at the cost of developing independent strategies; and critical appropriation, a rare but instructive pattern in which learners developed metacognitive awareness of how their own SRL was being shaped by tool access and actively worked to counterbalance AI dependency. The study draws on Zimmerman's SRL framework (Zimmerman, 2000; Zimmerman & Moylan, 2009) and Benson's (2011) conceptualisation of learner autonomy to argue that GenAI access does not uniformly promote or undermine learner autonomy in EFL academic writing—its effects depend substantially on the self-regulatory capacities learners bring to the interaction and the pedagogical scaffolding their programmes provide.